2014
DOI: 10.1111/pme.12377
|View full text |Cite
|
Sign up to set email alerts
|

Single-Entity Hydrocodone Extended-Release Capsules in Opioid-Tolerant Subjects with Moderate-to-Severe Chronic Low Back Pain: A Randomized Double-Blind, Placebo-Controlled Study

Abstract: Extended-release HC is well tolerated and effective, without acetaminophen-associated risks of liver toxicity, for treatment of CLBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 19 publications
4
49
0
Order By: Relevance
“…There was drug accountability with record keeping of drug administered and drug returned. Another study by Rauck et al [28] looked at the safety and efficacy of HC-ER tablets (Zohydro Ò ER; Zogenix, Inc., San Diego, CA, USA) in the relief of moderate to severe low back pain in opioid-experienced subjects. It was concluded that HC-ER is more effective than placebo as an analgesic and the tolerability and efficacy was maintained during the 12-week period of double-blind treatment.…”
Section: Zohydro Er òmentioning
confidence: 98%
“…There was drug accountability with record keeping of drug administered and drug returned. Another study by Rauck et al [28] looked at the safety and efficacy of HC-ER tablets (Zohydro Ò ER; Zogenix, Inc., San Diego, CA, USA) in the relief of moderate to severe low back pain in opioid-experienced subjects. It was concluded that HC-ER is more effective than placebo as an analgesic and the tolerability and efficacy was maintained during the 12-week period of double-blind treatment.…”
Section: Zohydro Er òmentioning
confidence: 98%
“…Rauck, et al [34] The mean change from screening to day 85 in SGAM (Subject Global Assessment of Medication) was 0.8 ± 1.3 for the HC-ER (hydrocodone extended release) group compared with 0.0 ± 1.4 for the placebo group (P < 0.001), indicating a significantly greater degree of satisfaction with HC-ER than with placebo.…”
Section: Chownmentioning
confidence: 99%
“…Others were randomised controlled trials (33%, n=9) [15,17,18,[31][32][33][34][35][36], before and after studies (11%, n=3) [37], and cross-sectional surveys (7%, n=2) [5,38].…”
Section: Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The committee also commented on the lack of data presented by Zogenix (Zohydro's manufacturer and sponsor of the clinical trials presented to the FDA) that could contribute to the characterization the responders in the study group, or facilitate the identification of responders in the general population. One committee member emphasized that the indication sought for approvalmoderate-to-severe chronic pain -was a generalized indication that gave prescribers no additional information or grounds for identifying the patients for which the drug would actually be effective, even though 41 per cent of those initially enrolled in the study were discontinued for poor tolerance or inadequate response, followed by an additional 18 per cent of those in the treatment arm of the study (Rauck et al, 2014;ClinicalTrials.gov, 2014).…”
Section: "Unsettling Circularity"mentioning
confidence: 99%